Factors Related to The Inaccessibility of HIV Tests for Women of Reproductive Age in Uzbekistan - Khan, Muhammad Uzair; Hastuti, Sari; Afriannisyah, Entan Afriannisyah (AMPLITUDO : Journal of Science and Technology Innovation, 2024)
HIV testing is important for women of reproductive age. It will be risky during the period of pregnancy, delivery, and breastfeeding and lead to MTCT (mother-to-child transmission) of HIV/AIDS. This study aimed to examine the factors associated with HIV testing. This study used MICS data that gathered the data from November 2021 to January 2022. The total respondents in this study were 1,893 women. The result revealed that 42.58% of women in this study found inaccessibility to HIV testing. The multivariate analysis found the impactful factors are living in rural areas, experienced more than one marriage, and husband/partner as the main decision maker in selecting health facilities, with AOR 1.29; 1.74; and 1.56, respectively. In sum, almost half of women of reproductive age in Uzbekistan cannot access HIV testing with experienced more than once marriage had the highest risk. A qualitative approach can be included in the future study.